Perlindungan Hukum Anak Korban Kekerasan Seksual - Ahmad Jamaludin (CIC Lembaga Riset dan Konsultan Sosial, 2021)
Child protection law is a state policy in guaranteeing the rights and obligations of the child itself, both regulated in private law and in public law and formal law in the sense of the process of enforcing the protection of the child. Child protection is an effort to maintain children's human rights so that they can continue to grow and develop into the hope and successor of the nation and state. Legal protection for victims is an obligation of the state and society that must be sought, be it government institutions, be it the police or child protection institutions or the community itself. This study aims to find out how to realize legal protection for child victims of sexual violence, to find out the obstacles faced in implementing legal protection and to find out what efforts are being made to overcome obstacles in the legal protection process for victims of child abuse so that justice and legal certainty fully implemented. This research was conducted using descriptive analysis method, namely providing researched data about the condition of the object under study, namely victims of sexual violence associated with statutory regulations, and normative juridical methods. The data obtained from library research is supported by field research, namely conducting interviews, then analyzed qualitatively. This research was conducted at Komnas Perempuan, the Center for Integrated Protection for the Empowerment of Women and Children (P2TP2A), and the Institute for Child Rights Advocacy (LAHA), the Indonesian National Commission for Child Protection. Based on the results of the study, it was concluded that legal protection for child victims of underage sexual abuse has not been fully realized because there are still children who have not received the rights regulated by law. Such as the rehabilitation process and getting the progress of the case and the resolution of the case. Constraints faced are obstacles regarding legal protection for child victims of sexual violence, namely legal protection for child victims of sexual violence in the form of obscenity, namely the process of completing difficult case investigations, low level of public awareness and lack of facilities in the investigation process. Meanwhile, efforts that can be done are to resolve cases quickly and according to the law, increase public awareness and coordinate with institutions that are related to the legal protection process for victims of sexual abuse as a form of sexual violence.